Efektivitas Creative Problem Solving untuk Meningkatkan Keterampilan Berpikir Kreatif - Fadkhurosi, Adnan (Edu Berkah Khatulistiwa, 2024)
The aim of the research carried out was to measure the effectiveness of creative problem solving (CPS) to improve the creative thinking skills of junior high school students in the city of Surakarta. The type of research methodology used is quantitative, which specifically carries out experimental research with a pre and post-test experimental research design, so that the research mechanism uses the experimental group as the test material and the control group as the measurement standard. The research was conducted on a sample of three junior high schools in the city of Solo, namely schools A, B, C and used an accumulated sample of 150 participants who were raised using a simple random sampling technique. The data collection techniques used were pre-test and post-test (questionnaire) and analyzed using descriptive quantitative analysis. The results of this research, namely Creative Problem Solving, were proven to be effective in improving students' creative thinking skills with a score obtained of 0.94 (high category). There are three gain score qualifications, namely below 0.3 is the low category; 0.3 to 0.7 is the medium category; and above 0.7 is a high category. So it can be concluded that the gain score of the research carried out is interpreted as a high category.